Analysis of Pick up and Slope Settings of Differential Relays on 60 MVA Power Transformers at Namorambe Substation - Muhammad Aditya; Siti Anisah; Haris Gunawan (Sean Institute, 2026)
This study analyzes the pickup and slope settings of differential relays used for the protection of a 60 MVA power transformer at the Namorambe Substation. Differential relays play an important role in detecting internal faults in transformers by comparing the current entering and leaving the protected zone. Improper relay settings may lead to maloperation, reduced system reliability, or failure to isolate faults, which can disrupt power system stability. Therefore, accurate determination of pickup current and slope characteristics is essential to ensure reliable transformer protection performance. The research method used in this study is a quantitative analysis approach based on transformer operational data, current transformer (CT) ratios, nominal transformer capacity, and relay parameter calculations. The pickup setting was determined by calculating the minimum differential current required for relay operation, while the slope setting was analyzed to maintain relay stability during external faults and magnetizing inrush currents. Data analysis was carried out by comparing calculation results with standard relay protection principles and transformer operating conditions. The results show that the selected pickup and slope settings provide effective protection sensitivity while maintaining system stability under normal and fault conditions. The relay is capable of distinguishing internal faults from transient disturbances, thereby minimizing false trips and improving transformer operational reliability. The study concludes that proper differential relay coordination on the 60 MVA transformer at Namorambe Substation significantly enhances protection performance and contributes to the continuity and safety of electrical power distribution systems.